2021
DOI: 10.3389/fnut.2021.748118
|View full text |Cite|
|
Sign up to set email alerts
|

Coral-Derived Endophytic Fungal Product, Butyrolactone-I, Alleviates Lps Induced Intestinal Epithelial Cell Inflammatory Response Through TLR4/NF-κB and MAPK Signaling Pathways: An in vitro and in vivo Studies

Abstract: Herein, we assessed the anti-inflammatory and intestinal barrier protective effects of butyrolactone-I (BTL-1), derived from the coral-derived endophytic fungus (Aspergillus terreus), using the LPS-induced IPEC-J2 inflammation model and the DSS-induced IBD model in mice. In IPEC-J2 cells, pretreatment with BTL-I significantly inhibited TLR4/NF-κB signaling pathway and JNK phosphorylation, resulting in the decrease of IL-1β and IL-6 expression. Interestingly, BTL-1 pretreatment activated the phosphorylation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…In recent years, many efforts have been devoted to discovering potent and selective BChE inhibitors through chemical design and synthesis ( Li et al, 2021 ; Rossi et al, 2021 ), or screening of natural products (NPs) and their derivatives ( Orhan et al, 2017 ; Jabir et al, 2018 ; Wu et al, 2019 ; Chen et al, 2021 ; Onder et al, 2022 ). Galantamine, isolated from the bulbs and the flowers of Galanthus woronowii , is an approved drug used for treating AD as a natural AChE inhibitor with relatively weak BChE inhibitory activity ( Marucci et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many efforts have been devoted to discovering potent and selective BChE inhibitors through chemical design and synthesis ( Li et al, 2021 ; Rossi et al, 2021 ), or screening of natural products (NPs) and their derivatives ( Orhan et al, 2017 ; Jabir et al, 2018 ; Wu et al, 2019 ; Chen et al, 2021 ; Onder et al, 2022 ). Galantamine, isolated from the bulbs and the flowers of Galanthus woronowii , is an approved drug used for treating AD as a natural AChE inhibitor with relatively weak BChE inhibitory activity ( Marucci et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…[55][56][57] Prior studies have shown that DSS reduced the expression of TJs in the gut epithelium of mice, and restoring the level of TJs could improve the homeostasis of the intestinal mechanical barrier and alleviate inflammatory bowel disease. [58][59][60] An in vivo study showed that DHAenriched PLs could increase the levels of TJ proteins ZO-1 and occludin, and thereby improved the intestinal barrier of DSS treatment injury. 61 This study is the first to show that EYPC can significantly inhibit DSS-induced reduction of colonic TJ expression and maintain intestinal barrier integrity.…”
Section: Papermentioning
confidence: 99%
“…Ocaña-Guzman et al reported that stress could hinder the body's delayed hypersensitivity reaction and reduce T lymphocyte conversion function, which may be caused by endogenous opioids. Also, the stress-induced inhibition of T lymphocyte reaction may be related to the Under HS, the gastric emptying time and the intensity of intestinal peristalsis of animals are prolonged and weakened, which reduces the mechanical digestive function, resulting in accumulation of chyme and inhibition of appetite [47] 8…”
Section: Effects Of Heat Stress On Immune Organs and Immunementioning
confidence: 99%